Lingwistyczny status hiszpanskich fuzji czasowników z zaimkami osobowymi - Machowski, Szymon (Investigationes Linguisticae, 2010)
The aim of this article is to describe and classify fusions of Spanish verbs with pronominal enclitics as simple words. Such a classification of fusions of Spanish verbs with pronominal enclitics is based on the analyses of prosodic properties of the verb-orginated and pronominaorginated constituents. Moreover, the prosodic properties influence the semantic properties of the verb-orginated and pronomina-orginated constituents.